Periodicals Received (Review of Economic Studies, 1939)
Journal Article Periodicals Received Get access The Review of Economic Studies, Volume 6, Issue 3, June 1939, Pages 238–239, https://doi.org/10.1093/restud/6.3.238 Published: 01 June 1939